Effects of hydrogen sulfide on inflammation in caerulein-induced acute pancreatitis - Bhatia Madhav; Ng Siaw; Sidhapuriwala Jenab N (BMC, 2009)
Abstract Background Hydrogen sulfide (H2S), a gaseous mediator plays an important role in a wide range of physiological and pathological processes. H2S has been extensively studied for its various roles in cardiovascular and neurological disorders. However, the role of H2S in inflammation is still controversial. The current study was aimed to investigate the therapeutic potential of sodium hydrosulfide (NaHS), an H2S donor in in vivo model of acute pancreatitis in mice. Methods Acute pancreatitis was induced in mice by hourly caerulein injections (50 μg/kg) for 10 hours. Mice were treated with different dosages of NaHS (5 mg/kg, 10 mg/kg or 15 mg/kg) or with vehicle, distilled water (DW). NaHS or DW was administered 1 h before induction of pancreatitis. Mice were sacrificed 1 h after the last caerulein injection. Blood, pancreas and lung tissues were collected and were processed to measure the plasma amylase, myeloperoxidase (MPO) activities in pancreas and lung and chemokines and adhesion molecules in pancreas and lung. Results It was revealed that significant reduction of inflammation, both in pancreas and lung was associated with NaHS 10 mg/kg. Further the anti-inflammatory effects of NaHS 10 mg/kg were associated with reduction of pancreatic and pulmonary inflammatory chemokines and adhesion molecules. NaHS 5 mg/kg did not cause significant improvement on inflammation in pancreas and associated lung injury and NaHS 15 mg/kg did not further enhance the beneficial effects seen with NaHS 10 mg/kg. Conclusion In conclusion, these data provide evidence for anti-inflammatory effects of H2S based on its dosage used.